2013
DOI: 10.1007/s11655-013-1454-2
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin as a Chinese medicine, selectively induces apoptosis in pancreatic tumor cell line

Abstract: Artemisinin can induce apoptosis in the RIN cells via the generation of ROS and triggering the intrinsic pathway of cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Previous studies have shown that artemisinin induced apoptosis in pancreatic tumor cells (36), lung adenocarcinoma cells (37), liver cancer cells (38), and non-small cell lung cancer cells (39). In the present study, we first demonstrated that artemisinin induced the cell death and apoptosis of neuroblastoma cells at a lower dose than that for clinical usage.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies have shown that artemisinin induced apoptosis in pancreatic tumor cells (36), lung adenocarcinoma cells (37), liver cancer cells (38), and non-small cell lung cancer cells (39). In the present study, we first demonstrated that artemisinin induced the cell death and apoptosis of neuroblastoma cells at a lower dose than that for clinical usage.…”
Section: Discussionsupporting
confidence: 59%
“…DHA and artesunate are the most studied ART derivatives for cancer treatment, and artesunate will be discussed in a separate section. The anti-cancer effects of ARTs are demonstrated in a broad spectrum of cancer cells including lung, liver, pancreatic, colorectal, esophageal, breast, ovarian, cervical, head and neck, and prostate cancers [183][184][185][186][187][188][189][190][191]. The anti-cancer activities of ARTs include induction of apoptosis and cell cycle arrest, inhibition of cell proliferation and growth, metastasis and angiogenesis [189,[192][193][194][195].…”
Section: Artemisininsmentioning
confidence: 99%
“…induced ROS-dependent apoptosis in human colon (DLD-1) and endometrium (ECC-1) cancer cells ( 31 ). The isolated sesquiterpenoid lactones from the genus Artemisia, like artemisinin and dihydroartemisinin, have been able to induce apoptosis in different cancerous cell lines ( 32 33 ). In contrast to the terpenoid extract of A. ciniformis , no sesquiterpene lactone has been detected in that of A. biennis ( 34 ).…”
Section: Discussionmentioning
confidence: 99%